The Neuropsychiatric Changes After COVID-19 Quarantine in Patients With Cognitive Impairment and Their Caregivers in Chongqing, China: A Cohort Study - Yuan, Shiyun; Zhang, Wenbo; Yao, Qiang; Lü, Wenqi; Yu, Wuhan; Zhong, Fuxin; Wang, Yan; Xing, Dianxia; Wang, Xiaoqin; Song, Jiaqi; Huang, Hong; Chen, Chenxi; et al. (Frontiers in Aging Neuroscience, 2022)
Abstract Background The follow-up study on neuropsychiatric changes after the lifting of COVID-19 quarantine in patients with cognitive impairment and their caregivers is still lacking, and relative information is needed to formulate more comprehensive healthcare prevention measures around the world. Aims To provide data on the changes of neuropsychiatric performance after the lifting of COVID-19 quarantine in patients with cognitive disorders and their caregivers. Methods Two surveys in Chongqing, China were conducted via telephone interview in 531 patients and their caregivers. The baseline survey was performed from February 11th to 23rd, 2020, and the follow-up was from October 24th to November 9th, 2020. The data of neuropsychiatric symptoms (NPSs), sleep, nutrition, and chronic diseases of patients, as well as the burden of care, anxiety and depression of caregivers were evaluated. Results Significant alleviation of NPSs after the lifting of COVID-19 quarantine were observed in patients with mild cognitive impairment (MCI) and dementia (both P 0.05). Compared to baseline, the prevalence for NPSs of all participants dropped from 57.94% to 38.82%. Among NPS subdomains, apathy displayed the biggest decline at follow-up by 10.72%, followed by nighttime behavior by 8.65%. Mixed Effect Generalized Estimation Equation analysis showed significant amelioration in hallucination, depression, apathy, irritability, aberrant motor behavior and nighttime behavior (all P 0.05), with the most prominent changes in nighttime behavior and apathy. Among the patients with unsatisfactory control of chronic disease, medication adherence rate dropped by approximately 30% after the lifting of quarantine. More importantly, around 13% increase of care burden was observed among the caregivers at follow-up, with both depression and anxiety rising by nearly 4%. Conclusion The prolonged quarantine may exacerbate NPS in patients with memory disorders, while the care burden and mental stability of the caregivers after the pandemic should also be concerned.